"The influence of Melody upon man in the wild state of nature": Enslaved Parishioners, Anglican Violence, and Racialized Listening in a Jamaica Parish. Issue 3 (August 2021) - Ryan, Maria
Abstract: In 1827, George Wilson Bridges, the outspoken proslavery rector of the parish of St. Ann, Jamaica, published a pamphlet of music that he had written to be used as the choral service at his church. The Bishop of Jamaica condemned Bridges's musical innovations on the grounds that they were not suitable to be heard by "a congregation chiefly composed by people of colour & negroes." On the Bishop's orders, Bridges's music stopped, and by 1828 he reported that his pews were once more empty. The congregation of St. Ann parish church was almost entirely enslaved Africans and Afro-descendants who could choose their place of worship. However, in Bridges's own household, the people he claimed as property had little opportunity to escape his ministering. In 1829 Bridges came to the attention of British abolitionists for his brutal flogging of Kitty Hylton, a woman he claimed to own. This article uses Black feminist approaches to archival materials to explore the relationship between the music promoted by Bridges, conflicting views held by white religious leaders about what music was appropriate for African and African-descended people to listen to, and Bridges's violence towards enslaved people; in so doing exploring the inescapable entanglement of religious music, race, and violence in colonial Jamaica.